Taiwan’s Path to Innovative R&D and Applications: Technology-Driven and Location-Driven Pilot Programs (International Journal of Automation and Smart Technology, 2012)
Pilot program has become a recent buzz term in the media and in business circles, especially in China where Taiwan is forging increasingly closer ties. Armed with massive regional markets, the pilot programs in China have attracted the earnest attention of multinational companies and government agencies hoping to expand their markets and improve industry development by participating in the early-stages of development. A pilot program usually refers to the development of a new product or application for a technical concept, or to the experimental operations of new business models, service models, policies, or systems in a specific region. The programs usually range in size from family or hospital use, to that of a community or city, with user feedback serving as a basis for subsequent improvement. This concept is similar in spirit and function to Living Labs, which were proposed by Massachusetts Institute of Technology Professor William Mitchell and have sparked a wave of innovative R&D and applications in Europe, the U.S., Japan, Korea, as well as in other countries. Both concepts emphasize employing a user-centered research method in various experience tests. This is done by observing users in live scenarios and then using feedback from their interaction with stakeholders (including governments, private enterprises, research organizations, and communities) to co-create value in the early-stages of innovation and creation, ultimately resulting in market-ready products or services.